Modeling Sprawling Locomotion of the Stem Amniote Orobates: An Examination of Hindlimb Muscle Strains and Validation Using Extant Caiman - Zwafing, Michelle; Lautenschlager, Stephan; Demuth, Oliver E.; Nyakatura, John A. (Frontiers in Ecology and Evolution, 2021)
The stem amniote Orobates pabsti has been reconstructed to be capable of relatively erect, balanced, and mechanically power-saving terrestrial locomotion. This suggested that the evolution of such advanced locomotor capabilities preceded the origin of crown-group amniotes. We here further investigate plausible body postures and locomotion of Orobates by taking soft tissues into account. Freely available animation software BLENDER is used to first reconstruct the lines of action of hindlimb adductors and retractors for Orobates and then estimate the muscle strain of these muscles. We experimentally varied different body heights in modelled hindlimb stride cycles of Orobates to find the posture that maximizes optimal strains over the course of a stride cycle. To validate our method, we used Caiman crocodilus. We emulated the identical workflow used for the analysis of Orobates and compared the locomotor posture predicted for Caiman based on muscle strain analysis with this species’ actual postural data known from a previously published X-ray motion analysis. Since this validation experiment demonstrated a close match between the modelled posture that maximizes optimal adductor and retractor muscle strain and the in-vivo posture employed by Caiman, using the same method for Orobates was justified. Generally, the use of muscle strain analysis for the reconstruction of posture in quadrupedal vertebrate fossils thus appears a promising approach. Nevertheless, results for Orobates remained inconclusive as several postures resulted in similar muscle strains and none of the postures could be entirely excluded. These results are not in conflict with the previously inferred moderately erect locomotor posture of Orobates and suggest considerable variability of posture during locomotion.